Sovereignty at the Paris Peace Conference of 1919 - Smith, Leonard V. 1957- (Oxford University Press, 2018)
While the Paris Peace Conference of 1919 failed, in that it couldn't prevent WWII, Leonard V. Smith's ground-breaking work shows how it was instrumental in creating a new kind of international cooperation where national sovereignty was used to remake a new world order
This edition previously issued in print: 2018. - Includes bibliographical references and index
Keywords: Paris Peace Conference / (1919-1920); Pariser Friedenskonferenz -- 1919-1920 -- Paris; Sovereignty / History / 20th century; Souveränität